195k views
3 votes
Solve for k. a/b=b/a+1/k

2 Answers

5 votes

Answer: K= ab/(a+b)(a-b)

User Rodzmkii
by
4.8k points
5 votes

Answer:

k = ab/ ( a^2 - b^2)

Explanation:

a/b=b/a+1/k

Multiply each side by abk to get rid of the fractions

abk *a/b=abk(b/a+1/k)

a^2k = b^2k + ab

Subtract b^2k from each side

a^2k - b^2k = b^2k - b^2k + ab

a^2 k - b^2 k = ab

Factor out k

k( a^2 - b^2) = ab

Divide each side by ( a^2 - b^2)

k( a^2 - b^2)/ ( a^2 - b^2) = ab/ ( a^2 - b^2)

k = ab/ ( a^2 - b^2)

User Changbin Du
by
5.5k points